Intact Stability Analysis of Crew Boat with Variation of Deadrise Angle - Putranto, Teguh; Suastika, Ketut; Gunanta, Julhari (Institut Teknologi Sepuluh Nopember, 2017)
AbstractÂ¾ As a supporter of offshore supply logistics operations, crew boat moving in high speed needs the hull design that is able to reduce the resistance but the stability is still good. The innovation of hull design carried out have to consider not only in aspect of safety and comfort, but also in aspect of cargo hold capacity. Therefore, this research will analyze the change of deadrise angle to the stability, cargo hold capacity, and resistance. The shift of weight and buoyancy point caused by the change of deadrise angle is calculated by block method. The calculation of cargo hold is carried out by integration of CSA curve. The calculation of ship stability is carried out by using the Krylov I method. If the stability varied by deadrise angle does still fulfill, the next analysis is the resistance. The resistance calculation uses Computational Fluid Dynamics (CFD). The smallest resistance is occurred with deadrise angle 16 degrees which the magnitude is 144.741 kN in speed 24 knots. The output obtained from this research is a recommendation of hull design revealing that crew boat with deadrise angle 6 degrees have an enough cargo hold to take up payload and the stability still fulfills the IMO Regulation.